Kontribusi Faktor Kompetensi, Sarana Prasarana, dan Motivasi Kerja Terhadap Kinerja Penyidik Direktorat Reserse Narkoba Polda Aceh - Nurhadi Al Akbar; Kamaruddin Kamaruddin (Aceh Cooperative Care, 2026)
A study of the performance of police officers, particularly investigators, is essential. This article examines the factors of investigator competence, infrastructure, and work motivation. A quantitative associative approach was used to analyze the problem, applying inferential statistics through the Path Analysis Model. A number 99 of investigators from the Aceh Regional Police Narcotics Research Directorate were used as respondents in a questionnaire to obtain data and information for the study. The findings revealed: (1) investigator performance is significantly influenced by direct and indirect effects through the causality of three factors: competence by 17.94%, infrastructure by 18.32%, and work motivation by 35.32%. (2) Investigator competence, infrastructure, and work motivation simultaneously contribute to an increase in investigator performance by 27,3%.